NORMATIVE DATA OF PENILE LENGTH ON CHILDREN AGE GROUPS WITH TANNER CLASSIFICATION IN HASAN SADIKIN HOSPITAL - Wallad, Caesar Khairul; Sibarani, Jupiter; Tjahjodjati, Tjahjodjati (Indonesian Urological Association, 2017)
Objective: It has been reported that normal value of penile length were varied among countries. Difference in race, ethnicity, genetics and nutrition plays a factor in penile length. Micropenis is an abnormality in which penile length were considered smaller in comparison of a ‘normal penile length’. There are published article in Asia and Europe in terms of local penile length figures unfortunately none in West Java. This study was aim to establish local data as a reference in order to define micropenis. Material & method: All subjects in pediatric outpatient clinics were collected with cross sectional method. Exclusion criteria includes: congenital penile disease (hypospadias, burried penis, chordee, fistulas, webbed, etc), history of hormonal therapy, malnourished, and congenital syndromes. Subjects will undergone examination of stretched penile length. Results: A total of 276 children were included in the study with 23 subjects in each Tanner groups. The average penile length in Hasan Sadikin Hospital were inferior in all groups in contrast with the Tanner age groups as cited in table 1. Conclusion: Normative local data of penile length is necessary. Not using the local reference may result in underestimation and overdiagnosis.